Polyphenylene sulfide composition and application thereof, cover body and preparation method thereof, battery and electric device

By using polyphenylene sulfide composition in the battery cover, combining inorganic minerals, glass fibers and amorphous polymers, the shortcomings of the battery cover in terms of strength, warpage and ablation resistance are solved, and a higher degree of resistance is achieved The mechanical strength and ablation resistance are suitable for battery packaging structures in high temperature environments.

CN119432075APending Publication Date: 2025-02-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310953010.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing battery cover has shortcomings in strength, warpage and ablation resistance, and it is difficult to meet the performance requirements under high-temperature flames.

Method used

A polyphenylene sulfide composition is adopted, including 30 parts by weight to 60 parts by weight of the polyphenylene sulfide resin, 10 parts by weight to 30 parts by weight of inorganic mineral, 30 parts by weight to 40 parts by weight of glass fiber and 5 parts by weight of ~15 parts by weight of a non-crystalline polymer, through the combination of these components, the dimensional stability, mechanical strength and ablation resistance of the composition are improved.

Benefits of technology

The polyphenylene sulfide composition has high mechanical strength, good ablation resistance and low warpage, and can effectively extend the melting time under high temperature flame, and is suitable for packaging structures of products such as batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432075A_ABST
    Figure CN119432075A_ABST
Patent Text Reader

Abstract

The invention discloses a polyphenylene sulfide composition and application thereof, a cover body and a preparation method thereof, a battery and an electric device. The polyphenylene sulfide composition is prepared from the following components in parts by weight: 30 to 60 parts of polyphenylene sulfide resin, 10 to 30 parts of inorganic mineral, 30 to 40 parts of glass fiber and 5 to 15 parts of amorphous polymer. The composition has better flame retardance and ablation resistance, higher mechanical strength and lower warping degree, and can be widely applied to packaging structures of products such as batteries and the like, for example, the composition can be used for preparing a cover body of a battery pack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of batteries, and specifically, relates to a polyphenylene sulfide composition and its use, a cover and its preparation method, a battery and an electrical device. Background Art

[0002] As an energy storage device, batteries are widely used in various fields. Take lithium-ion batteries as an example. They are green, environmentally friendly, high-energy, and low-carbon. They are not only used in energy storage power systems such as hydropower, thermal, wind, and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, and ships, as well as military equipment and aerospace and other fields. With the development of the current society, people's requirements for batteries are getting higher and higher. Summary of the invention

[0003] In view of the technical problems existing in the background technology, the present application provides a polyphenylene sulfide composition, which aims to improve the strength, warpage and ablation resistance of a battery cover.

[0004] In order to achieve the above-mentioned objectives, the first aspect of the present application provides a polyphenylene sulfide composition, comprising: 30 to 60 parts by weight of polyphenylene sulfide resin, 10 to 30 parts by weight of inorganic minerals, 30 to 40 parts by weight of glass fiber, and 5 to 15 parts by weight of a non-crystalline polymer.

[0005] The polyphenylene sulfide composition of the present application has the following beneficial effects: the introduction of inorganic minerals and non-crystalline polymers can improve the dimensional stability of the composition and reduce the warpage; combined with the good flame retardancy and mechanical strength of polyphenylene sulfide itself, under the reinforcement of glass fiber and inorganic minerals, the composition can have both high mechanical strength and good ablation resistance, effectively prolonging the melting time of polyphenylene sulfide under high temperature flame. Therefore, the composition has good flame retardancy and ablation resistance, high mechanical strength and low warpage, and can be widely used in the packaging structure of products such as batteries, for example, it can be used to prepare the cover of the battery pack, eliminating the mica paper and edge strips in the battery pack cover.

[0006] In some embodiments of the present application, the polyphenylene sulfide composition includes: 30 to 45 parts by weight of the polyphenylene sulfide resin, 10 to 25 parts by weight of the inorganic mineral, 35 to 40 parts by weight of the glass fiber, and 8 to 12 parts by weight of the non-crystalline polymer.

[0007] In some embodiments of the present application, the crystallization temperature of the polyphenylene sulfide resin is less than or equal to 225° C. Meeting the given conditions is conducive to improving the fluidity and processability of the polyphenylene sulfide composition, and reducing the difficulty and production cost of preparing specific structural parts using the composition.

[0008] In some embodiments of the present application, the melt index of the polyphenylene sulfide resin at a temperature of 316° C. and a mass of 5 kg is 400 g / 10 min to 1200 g / 10 min, and can be 600 g / 10 min to 800 g / 10 min. Meeting the given conditions is conducive to improving the fluidity and processability of the polyphenylene sulfide composition, and reducing the difficulty and production cost of preparing specific structural parts using the composition.

[0009] In some embodiments of the present application, the non-crystalline polymer includes at least one of polystyrene, polyarylethernitrile, polyphenylene oxide, polysulfone, polyetherimide, polyphenylene sulfone, polyethersulfone or polyimide. Optionally, the non-crystalline polymer includes polystyrene and / or polyarylethernitrile. The composition of the non-crystalline polymer satisfies the given range, which is conducive to taking into account both low warpage and high fluidity of the polyphenylene sulfide composition.

[0010] In some embodiments of the present application, the glass fiber includes short fibers and / or flat fibers. Controlling the composition of the glass fiber to meet the given range requirements is beneficial to further consider the mechanical strength and dimensional stability of the polyphenylene sulfide composition.

[0011] In some embodiments of the present application, the length of the short fiber is 3 mm to 4.5 mm, and the diameter is 7 μm to 13 μm; and / or the flatness ratio of the flat fiber is less than or equal to 1 / 4, and the diameter is 7 μm to 13 um.

[0012] In some embodiments of the present application, the polyphenylene sulfide composition further includes: a silane coupling agent, based on the total mass of the inorganic mineral and the glass fiber, the mass percentage of the silane coupling agent in the inorganic mineral and the glass fiber is ≤1wt%, and can be 0.5wt% to 1wt%. Controlling the amount of the silane coupling agent to meet the given range can further reduce the raw material cost on the basis of improving the compatibility and dispersibility of the inorganic mineral and the glass fiber with the polyphenylene sulfide resin and the non-crystalline polymer.

[0013] In some embodiments of the present application, the polyphenylene sulfide composition further comprises: at least one of a toughening agent, a lubricant, an antioxidant, a color powder or a laser engraving aid. Making the composition of the polyphenylene sulfide composition meet the given range is conducive to further improving the performance, appearance or processability of the polyphenylene sulfide composition.

[0014] The second aspect of the present application provides a cover, which includes: the polyphenylene sulfide composition of the first aspect of the present application. The cover has good flame retardancy and ablation resistance, good strength, good dimensional stability, high flatness, and is conducive to improving the sealing effect. It can be widely used as a packaging structure for products such as batteries, for example, it can be used as a cover for a battery pack, eliminating the mica paper and edge strips in the battery pack cover.

[0015] In some embodiments of the present application, the cover body includes: a cover plate and a side wall, the side wall is connected to the cover plate to enclose a receiving area, and the material of the cover plate and / or the side wall includes the polyphenylene sulfide composition of the first aspect of the present application. Controlling the cover body to meet the given conditions is conducive to further making the cover body have better flame retardancy and ablation resistance, better strength, good dimensional stability, high flatness, which is conducive to improving the sealing effect, and has better processability.

[0016] In some embodiments of the present application, the thickness of the cover plate is ≤3mm, and can be 2mm to 3mm; and / or the thickness of the side wall is ≤3mm, and can be 2mm to 3mm. The cover body that meets the given conditions is not only thin, but also has good flame retardancy and ablation resistance even without mica paper and edge strips, and has high mechanical strength, good dimensional stability, and low warping.

[0017] In some embodiments of the present application, the cover plate and the side wall are integrally formed.

[0018] The third aspect of the present application provides a method for preparing a cover, which comprises: injection molding the polyphenylene sulfide composition of the first aspect of the present application to obtain a cover.

[0019] The fourth aspect of the present application provides a battery, which includes: the cover body of the second aspect of the present application or the cover body obtained by the preparation method of the third aspect of the present application.

[0020] The fifth aspect of the present application provides an electrical device, which includes: the battery of the fourth aspect of the present application.

[0021] The sixth aspect of the present application provides the use of the polyphenylene sulfide composition of the first aspect of the present application in structural parts in the fields of batteries, vehicles, chemicals, ships, and aerospace.

[0022] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0024] Figure 1 It is a schematic structural diagram of a cover body according to an embodiment of the present application.

[0025] Figure 2 It is a schematic structural diagram of a battery according to one embodiment of the present application.

[0026] Figure 3It is a schematic structural diagram of a battery module according to one embodiment of the present application.

[0027] Figure 4 It is a schematic diagram of the structure of a battery pack according to one embodiment of the present application.

[0028] Figure 5 is an exploded view of a battery pack according to one embodiment of the present application.

[0029] Figure 6 It is a schematic diagram of an embodiment of an electric device using a battery as a power source according to an embodiment of the present application.

[0030] Description of reference numerals:

[0031] 1: secondary battery; 2: battery module; 3: battery pack; 4: cover; 41: cover plate; 42: side wall; 5: lower box. DETAILED DESCRIPTION

[0032] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0033] Hereinafter, the polyphenylene sulfide composition and its use, the cover and its preparation method, the battery and the electric device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0034] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit, and the selected lower limit and / or upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end value, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form an unambiguous range, and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each individually disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0035] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0036] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0037] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S1 and S2, which means that the method may include steps S1 and S2 performed sequentially, or may include steps S2 and S1 performed sequentially. For example, the method may also include step S3, which means that step S3 may be added to the method in any order. For example, the method may include steps S1, S2 and S3, or may include steps S1, S3 and S2, or may include steps S3, S1 and S2, etc.

[0038] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0039] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0040] If there is no special explanation, in this application, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0041] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0042] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions. Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0043] With the continuous advancement of the green environmental protection theme, the application of batteries (such as lithium-ion batteries) has penetrated into all aspects of life, including vehicles, electronic equipment, energy storage devices, etc. The core components of new energy vehicles include power battery packs. The battery pack box generally includes a lower box and an upper cover, which are mainly used to protect the power battery from damage when it is hit or squeezed by the outside world. As the carrier of the battery module, the battery pack box plays a key role in the safe operation and protection of the battery module. With the continuous innovation of new energy vehicle technology and the increasing demand of consumers for driving range, the requirements for battery capacity are getting higher and higher, the risk of thermal runaway is getting more and more serious, and new energy vehicle combustion and explosion accidents occur from time to time. At present, the external thermal runaway of the battery cell mainly relies on the external design of mica paper and the upper cover to be isolated and protected by bonding with a cross-linking agent or a pressure-sensitive adhesive. Mica paper can reduce the risk of melting through the plastic parts of the upper cover due to thermal runaway. However, adding mica paper to the external protection of the battery cell will increase the cost. In addition, the bonding of mica paper and the upper cover often fails due to debonding. In addition, lightweighting is also an important direction of existing battery design. Existing box materials usually need to have both light weight and thermal runaway resistance. Polyphenylene sulfide composite materials have the performance advantages of cost-effectiveness, flame retardancy and high mechanical strength. They are ideal materials for preparing large thin-walled boxes. For example, there is currently a solution for preparing the upper cover using glass fiber reinforced polyphenylene sulfide, but due to the crystallinity of polyphenylene sulfide and the orientation of glass fiber, the prepared upper cover is prone to warping and deformation, causing the edge of the upper cover and the assembly surface of the lower box to be not in the same plane, affecting the airtightness of the box after assembly. At present, in order to solve the problem of thin-walled plastic covers being prone to warping, it is usually necessary to set metal edge strips on the side wall edges of the covers. However, the design of metal edge strips will increase the cost and difficulty of the manufacturing process. For example, the energy storage cover currently uses halogen-free flame-retardant polypropylene + mica paper and edge strips to meet the technical requirements of delayed thermal runaway and airtightness, but the preparation process is complicated and there is a risk of thermal runaway and airtightness failure.

[0044] In the present application, the polyphenylene sulfide resin is modified by using glass fiber, inorganic minerals and non-crystalline polymers in a preset ratio, which can improve the dimensional stability of the composition and reduce the warpage; at the same time, combined with the good flame retardancy and mechanical strength of polyphenylene sulfide itself, under the reinforcement of glass fiber and inorganic minerals, the obtained composition can have both high mechanical strength and good ablation resistance, which can effectively prolong the melting time of polyphenylene sulfide under high temperature flame. As a result, the modified polyphenylene sulfide composition has good flame retardancy and ablation resistance, high mechanical strength and low warpage, and can be widely used in the packaging structure of products such as batteries. When it is used to prepare the cover of the battery pack, the structural design of mica paper and metal edge strips can also be omitted.

[0045] The polyphenylene sulfide composition disclosed in the embodiments of the present application is suitable for structural parts in the fields of batteries, vehicles, chemicals, ships, aerospace, etc., including but not limited to the upper cover or box structure of energy storage devices such as battery packs, battery pack liners, vehicle protective plates, wind shields, fire doors, high-frequency connectors, etc., and is particularly suitable for large upper covers, large flat brackets, or large plastic structures with corners and depth that are difficult to prepare in actual production processes, as well as structural parts with high requirements for low warpage, ablation resistance, high strength, etc.

[0046] The first aspect of the present application provides a polyphenylene sulfide composition, comprising: 30 to 60 parts by weight of a polyphenylene sulfide resin, 10 to 30 parts by weight of an inorganic mineral, 30 to 40 parts by weight of glass fiber, and 5 to 15 parts by weight of a non-crystalline polymer.

[0047] In the polyphenylene sulfide composition of the present application, inorganic minerals and non-crystalline polymers are mainly used to improve the dimensional stability of the composition and reduce the warpage. Among them, the introduction of inorganic minerals can not only improve the mechanical strength of the composition, but also reduce the anisotropy caused by the orientation of glass fibers; the introduction of non-crystalline polymers can reduce the crystallinity of polyphenylene sulfide and reduce the uneven shrinkage caused by crystallization, thereby reducing the orientation degree of the composition and reducing the warpage. The combination of the two can significantly improve the dimensional stability of the composition and reduce its warpage. In addition to reinforcing the polyphenylene sulfide, the introduction of glass fibers in the polyphenylene sulfide composition of the present application is more importantly used to improve the ablation resistance of the composition. The glass fibers themselves have good high temperature resistance and cannot burn by themselves. At high temperatures, they can be combined with inorganic minerals to form a rigid mesh structure. By introducing enough glass fibers and combining the good flame retardancy and mechanical strength of polyphenylene sulfide itself, on the one hand, the combustion of the composition can be suppressed, and on the other hand, it is conducive to the glass fibers forming a continuous mesh support structure with inorganic minerals inside the composition, so that the composition is not easily melted through under high temperature flames, thereby improving the ablation resistance of the composition.

[0048] According to the embodiments of the present application, in the polyphenylene sulfide composition, the weight fraction of the polyphenylene sulfide resin can be 30, 35, 40, 45, 50, 55, 60, etc., or can be a range consisting of any of the above values; the weight fraction of the inorganic mineral can be 10, 15, 20, 25, 30, etc., or can be a range consisting of any of the above values; the weight fraction of the glass fiber can be 30, 32, 35, 38, 40, etc., or can be a range consisting of any of the above values; the weight fraction of the non-crystalline polymer can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, etc., or can be a range consisting of any of the above values. Among them, controlling the content of glass fiber in the composition to meet the given range can not only improve the mechanical strength of the composition and improve the ablation resistance of the composition, but also significantly reduce the risks of increased warpage of the composition, increased brittleness of the composition affecting mechanical properties, increased viscosity of the composition causing decreased fluidity, and thus increased difficulty in preparation, which may be caused by excessive use of glass fiber; controlling the amount of inorganic minerals to meet the given range can not only improve the mechanical strength of the composition, and improve the warpage and ablation resistance of the composition, but also significantly reduce the risks of increased brittleness of the composition affecting mechanical properties, increased viscosity of the composition causing decreased fluidity, and thus increased difficulty in preparation, which may be caused by excessive use of inorganic minerals; controlling the amount of non-crystalline polymers to meet the given range can not only effectively reduce the crystallinity of polyphenylene sulfide, reduce the uneven shrinkage caused by crystallization, and reduce the warpage of the composition, but also reduce the risk of excessive use of polyphenylene sulfide leading to a decrease in the relative amount of polyphenylene sulfide, thereby leading to a decrease in the limit amount of inorganic minerals and glass fibers that can be accommodated in the composition, and affecting the dimensional stability of the composition.

[0049] In the polyphenylene sulfide composition of the present application, each component can be qualitatively or quantitatively analyzed by one or more conventional means such as infrared spectroscopy, X-ray fluorescence spectroscopy, thermogravimetric analysis, differential scanning calorimetry, gas phase-mass spectrometry, EDS energy spectrum analysis, etc. For example, the polyphenylene sulfide composition sample can be subjected to infrared spectroscopy test, and whether the composition contains polyphenylene sulfide can be judged based on the characteristic peaks of the infrared spectrum, and whether the composition contains non-crystalline polymer can be judged by testing the melting curve by differential scanning calorimeter, and / or the polyphenylene sulfide composition sample can be dissolved in chloroform and then subjected to GC-MS (gas phase-mass spectrometry) total ion flow analysis to further judge the characteristic functional group information and content of polyphenylene sulfide and non-crystalline polymer; the polyphenylene sulfide composition sample can be ablated at 700°C for 1 hour, and the ash after ablation can be tested by infrared spectroscopy. The type of inorganic mineral can be determined, and the specific element content of the mineral can be determined by combining X-ray fluorescence spectroscopy (XRF) to determine the specific type of the mineral. The morphology and elemental analysis of the ash after ablation using a scanning electron microscope and an EDS spectrometer can be used to determine whether glass fiber exists and the content of the glass fiber. The component type of the composition obtained based on the qualitative analysis can be combined with thermal gravimetric analysis TGA and ablated ash tests to determine the content of inorganic matter and the content of polymer, and the decomposition weight loss curve and the weight loss at different temperatures can be combined to determine the amount of polyphenylene sulfide and non-crystalline polymer added.

[0050] The polyphenylene sulfide composition of the present application has the following beneficial effects: the introduction of inorganic minerals and non-crystalline polymers can reduce the crystallinity of polyphenylene sulfide, improve the dimensional stability of the composition, and reduce the warpage; combined with the good flame retardancy and mechanical strength of polyphenylene sulfide itself, under the reinforcement of glass fiber and inorganic minerals, the composition can have both high mechanical strength and good ablation resistance, effectively prolonging the melting time of polyphenylene sulfide under high temperature flame. Therefore, the composition has good flame retardancy and ablation resistance, high mechanical strength and low warpage, and can be widely used in the packaging structure of products such as batteries, for example, it can be used to prepare the cover of the battery pack, eliminating the mica paper and edge strips in the battery pack cover.

[0051] Furthermore, after in-depth research, it is found that the polyphenylene sulfide composition of the first aspect of the present application can further control the dosage ratio of each component, the crystallization temperature or melt index of the polyphenylene sulfide resin, the specific type of non-crystalline polymer, the size of the glass fiber, etc. on the basis of satisfying the above conditions to further optimize the performance of the polyphenylene sulfide composition. That is, on the basis of satisfying the above conditions, one or more of the following conditions can also be optionally satisfied.

[0052] In some embodiments of the present application, the ablation resistance of the polyphenylene sulfide composition can meet the following requirements: a 2mm to 3mm thick planar structural part made of the polyphenylene sulfide composition can be kept at 1000℃ to 1100℃ flame spray for 10 minutes without perforation and collapse. The polyphenylene sulfide composition that meets this requirement has good flame retardancy and ablation resistance. When it is used for the battery pack cover or box, it can prolong the melting time, delay the occurrence of thermal runaway, and save the structural design of mica paper. In addition, the polyphenylene sulfide composition of the present application has both good mechanical strength and low warpage. When it is used for packaging structural parts, it can obtain higher strength and better dimensional stability. Taking the cover of the battery pack as an example, when the polyphenylene sulfide composition is used to prepare the cover, on the one hand, it can obtain better dimensional stability and flatness, improve the fit and sealing effect with the sealing strip, reduce the risk of upper cover sealing failure, and also facilitate mechanical automatic assembly to reduce labor costs; on the other hand, the mechanical strength of the prepared cover is high, and the edge strength can be further enhanced through structural design, and the structural design of the cover pressure strip can be cancelled.

[0053] In some embodiments of the present application, the polyphenylene sulfide composition may include: 30 to 45 parts by weight of polyphenylene sulfide resin, 10 to 25 parts by weight of inorganic minerals, 35 to 40 parts by weight of glass fiber, and 8 to 12 parts by weight of non-crystalline polymer.

[0054] For example, the polyphenylene sulfide composition may include 30, 32, 35, 37, 39, 41, 43, 45 or other parts by weight of polyphenylene sulfide resin, 10, 12, 15, 17, 19, 21, 23 or 25 or other parts by weight of inorganic minerals, 35, 36, 37, 38, 39, 40 or other parts by weight of glass fibers, and 8, 9, 10, 11, 12 or other parts by weight of non-crystalline polymers.

[0055] By making the amount of each component meet the given range requirements, it can be further beneficial for the polyphenylene sulfide composition to have good flame retardancy and ablation resistance, high mechanical strength and dimensional stability, and low warpage.

[0056] In some embodiments of the present application, the crystallization temperature of the polyphenylene sulfide resin may be less than or equal to 225°C.

[0057] For example, the crystallization temperature of the polyphenylene sulfide resin may be less than or equal to 225°C, less than or equal to 215°C, less than or equal to 200°C, less than or equal to 180°C, etc. The crystallization temperature of the polyphenylene sulfide resin may be tested by conventional methods in the art, for example, a differential scanning calorimeter may be used in accordance with GB / T 33466.1-2016 or GB T 19466.3-2004; for another example, the polyphenylene sulfide resin may be heated from 30°C to 300°C at a rate of 10°C / min, held for 2 minutes, then cooled from 300°C to 30°C, held for 2 minutes, and then heated from 30°C to 300°C, and the temperature was obtained by measuring the thermal history of the sample based on differential scanning calorimetry (DSC). The polyphenylene sulfide resin with a low crystallization temperature is beneficial to improving the fluidity of the polyphenylene sulfide composition, reducing its processing mold temperature (such as reducing it from 130°C to 160°C to 100°C for molding), improving the processability of the composition, and is beneficial to using injection molding technology to replace the existing blow molding and compression molding methods to prepare specific structural parts. This not only improves the processing efficiency, but also helps reduce the difficulty and production cost of preparing specific structural parts using the composition, and is also beneficial to obtaining a better structural appearance.

[0058] By making the crystallization temperature of the polyphenylene sulfide resin meet the given conditions, it is beneficial to improve the processability of the polyphenylene sulfide composition and reduce the difficulty and production cost of preparing specific structural parts using the composition.

[0059] In some embodiments of the present application, the melt index of the polyphenylene sulfide resin at a temperature of 316° C. and a mass of 5 kg is 400 g / 10 min to 1200 g / 10 min, and can be optionally 600 g / 10 min to 800 g / 10 min.

[0060] For example, the melt index of polyphenylene sulfide resin at a temperature of 316° C. and a mass of 5 kg may be 400 g / 10 min, 500 g / 10 min, 600 g / 10 min, 700 g / 10 min, 800 g / 10 min, 900 g / 10 min, 1000 g / 10 min, 1100 g / 10 min, 1200 g / 10 min, etc., or may be a range consisting of any of the above values. The melt index of polyphenylene sulfide resin may be tested by conventional methods in the art, for example, with reference to GB / T 3682-2000, with a test temperature of 316° C. and a nominal load of 5 kg. Increasing the melt index of the polyphenylene sulfide resin is also beneficial to improving the fluidity of the polyphenylene sulfide composition, reducing its processing mold temperature (such as reducing it from 130°C to 160°C to 100°C for molding), improving the processability of the composition, and controlling the melt index of the polyphenylene sulfide resin to meet the given range can not only make the polyphenylene sulfide composition have better fluidity, but also reduce the injection molding material defects caused by the poor processability of the polyphenylene sulfide composition due to the low melt index of the polyphenylene sulfide resin, which leads to an adverse effect on the mechanical strength, and can better balance the processability and mechanical strength of the polyphenylene sulfide composition. Optionally, the melt index of the polyphenylene sulfide resin at a temperature of 316°C and a mass of 5kg can be 600g / 10min to 800g / 10min.

[0061] By making the melt index of the polyphenylene sulfide resin meet the given conditions, the processability and mechanical strength of the polyphenylene sulfide composition can be better balanced, which can not only reduce the difficulty and production cost of preparing specific structural parts using the composition, but also help to obtain better dimensional stability.

[0062] In some embodiments of the present application, the amount and ratio of each raw material component in the polyphenylene sulfide composition and the selection of the polyphenylene sulfide resin are controlled to meet the given range, so that the fluidity of the polyphenylene sulfide composition can reach 110g / 10min to 170g / 10min, such as 110g / 10min, 120g / 10min, 130g / 10min, 140g / 10min, 150g / 10min, 160g / 10min or 170g / 10min. Among them, the fluidity of the polyphenylene sulfide composition is tested with reference to the ISO 1133 standard method. The polyphenylene sulfide composition of the present application has a significantly improved fluidity compared with similar materials at 50g / 10min to 80g / 10min, and can be used to prepare large thin-walled structural parts through injection molding, and has good process feasibility in the preparation project.

[0063] In some embodiments of the present application, the non-crystalline polymer includes at least one of polystyrene (PS), polyarylether nitrile (PEN), polyphenylene oxide (PPO), polysulfone (PSU), polyetherimide (PEI), polyphenylene sulfone (PPSU), polyethersulfone (PES) or polyimide (PI). Optionally, the non-crystalline polymer includes polystyrene (PS) and / or polyarylether nitrile (PEN).

[0064] The non-crystalline polymer in the given range has good compatibility with the polyphenylene sulfide resin and a relatively low melting point. Using it in the polyphenylene sulfide composition is not only beneficial to reducing the crystallinity of the polyphenylene sulfide composition, improving the dimensional stability of the composition, and reducing the warpage, but also beneficial to improving the fluidity of the polyphenylene sulfide composition and improving the processability of the composition. In addition, PEN, PPO, PSU, PEI, PPSU, PES, and PI all have the characteristics of high limiting oxygen index. Using them in the polyphenylene sulfide composition is also beneficial to further improve the flame retardant effect and ablation resistance of the composition. By making the composition of the non-crystalline polymer meet the given range, it is beneficial to further take into account the low warpage and high fluidity of the polyphenylene sulfide composition.

[0065] Alternatively, the non-crystalline polymer may include polystyrene and / or polyarylethernitrile, and further optionally, the non-crystalline polymer may include polystyrene and polyarylethernitrile mixed in any proportion, polystyrene has a lower melting point, polyarylethernitrile not only has self-flame retardancy, but also has good mechanical properties and dimensional stability, and the combination of the two can take into account the processability, flame retardancy and dimensional stability of the polyphenylene sulfide composition at the same time, thereby further facilitating the acquisition of a polyphenylene sulfide composition having good mechanical strength, flame retardancy and ablation resistance, and low warpage. Optionally, polystyrene may include high-impact polystyrene, and the selection of high-impact polystyrene is conducive to further improving the mechanical strength of the polyphenylene sulfide composition.

[0066] In some embodiments of the present application, the glass fibers may include short fibers and / or flat fibers.

[0067] Compared with the milled fibers, the lengths of the short fibers and the flat fibers are relatively long, which is beneficial to further improve the reinforcing effect on the polyphenylene sulfide; optionally, the glass fibers may include flat fibers, which are also beneficial to reduce the effect on the warpage of the polyphenylene sulfide composition compared with the short fibers. The morphology of the glass fibers can be observed using an electron microscope SEM, and specifically, the polyphenylene sulfide composition can be ablated to remove the polymer components under conditions lower than the melting temperature of the glass fibers, such as ablation of the polyphenylene sulfide composition at 700°C for 1 hour, and the ash after ablation can be tested using an electron microscope SEM to observe the fiber morphology in the ash.

[0068] Controlling the composition of the glass fiber to meet the given range requirements is beneficial to further taking into account the mechanical strength and dimensional stability of the polyphenylene sulfide composition.

[0069] In some embodiments of the present application, the length of the short fiber may be 3 mm to 4.5 mm, and the diameter may be 7 μm to 13 μm; and / or the flatness ratio of the flat fiber may be less than or equal to 1 / 4, and the diameter may be 7 μm to 13 um.

[0070] For example, the length of the short fiber can be 3 mm, 3.5 mm, 4 mm, 4.5 mm, etc., and the diameter can be 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, etc.; for another example, the flatness ratio of the flat fiber can be less than or equal to 1 / 4, less than or equal to 1 / 5, less than or equal to 1 / 6, less than or equal to 1 / 7, less than or equal to 1 / 8, etc., and the diameter can be 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, etc. The flatness ratio can be understood as the ratio of the width of the fiber cross section to the length of the fiber cross section.

[0071] The size of the short fibers and flat fibers can be measured by electron microscope (SEM) gauge length measurement. For example, the polyphenylene sulfide composition can be ablated at 700° C. for 1 h, and the fiber size in the ash after ablation can be observed by electron microscope (SEM) and the gauge length can be measured.

[0072] By ensuring that the sizes of short fibers and flat fibers meet the given range, it is beneficial to take into account both the mechanical strength and dimensional stability of the polyphenylene sulfide composition, and to form a network structure in the composition, thereby improving the ablation resistance of the composition. At the same time, it can also reduce the limitation of the fiber length on the molding process, which is more conducive to the injection molding of the polyphenylene sulfide composition.

[0073] In some embodiments of the present application, the polyphenylene sulfide composition may further include: a silane coupling agent. Based on the total mass of the inorganic mineral and the glass fiber, the mass percentage of the silane coupling agent in the inorganic mineral and the glass fiber may be ≤1wt%, and may be optionally 0.5wt% to 1wt%.

[0074] For example, based on the total mass of the inorganic mineral and the glass fiber, the mass percentage of the silane coupling agent in the inorganic mineral and the glass fiber can be 1wt%, 0.9wt%, 0.8wt%, 0.7wt%, 0.6wt%, 0.5wt%, 0.4wt%, 0.3wt%, 0.2wt%, 0.1wt%, etc., or can be a range composed of any of the above values, which can be selected as 0.5wt% to 1wt%. The introduction of the silane coupling agent into the polyphenylene sulfide composition is beneficial to improve the compatibility and dispersibility of the inorganic mineral and the glass fiber with the polyphenylene sulfide resin and the non-crystalline polymer, reduce the risk of agglomeration of the inorganic mineral and the glass fiber in the polyphenylene sulfide composition, and improve the uniformity and mechanical properties of the polyphenylene sulfide composition. In the actual operation process, the inorganic mineral and / or the glass fiber can be surface treated with the silane coupling agent, and then mixed with other raw material components to prepare the polyphenylene sulfide composition. The qualitative and quantitative analysis of the silane coupling agent in the polyphenylene sulfide composition can also be performed by one or more conventional means such as infrared spectroscopy, gas chromatography-mass spectrometry, etc. For example, the soluble matter of the polyphenylene sulfide composition sample can be dissolved in chloroform and then subjected to GC-MS (gas chromatography-mass spectrometry) total ion flow analysis to further determine the characteristic information and content of the silane coupling agent.

[0075] By controlling the amount of the silane coupling agent to meet the given range, the cost of raw materials can be further reduced on the basis of improving the compatibility and dispersibility of the inorganic minerals and glass fibers with the polyphenylene sulfide resin and the non-crystalline polymer.

[0076] In some embodiments of the present application, the specific type of inorganic mineral in the polyphenylene sulfide composition is not particularly limited, and those skilled in the art can flexibly select it according to actual needs, for example, it can include but is not limited to at least one of calcium carbonate, calcium sulfate, barium sulfate, magnesium sulfate, talc, kaolin, mica, wollastonite, and glass beads. Further, in the polyphenylene sulfide composition of the present application, the size and morphology of the inorganic mineral used are not particularly limited, and those skilled in the art can flexibly select or adopt the conventional settings in the field according to actual needs. For example, the size range of the inorganic mineral can be micro-nano, such as including micron particles and / or nanoparticles. Meeting this range requirement is conducive to further improving the dispersibility of the inorganic mineral in the polyphenylene sulfide composition. Alternatively, the inorganic mineral can be provided in the form of particles and / or whiskers. Alternatively, the inorganic mineral can include an inorganic mineral modified by silane coupling.

[0077] In some embodiments of the present application, the polyphenylene sulfide composition may further include at least one of a toughening agent, a lubricant, an antioxidant, a color powder, and a laser engraving aid.

[0078] Adding a toughening agent is beneficial to improving the toughness of the polyphenylene sulfide composition. The toughening agent may include a polyolefin elastomer and / or a polyolefin elastomer grafted with maleic anhydride. For example, the toughening agent may include at least one of styrene grafted maleic anhydride copolymer, ethylene-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methacrylate copolymer, ethylene-methyl methacrylate-glycidyl methacrylate copolymer, ethylene-1-butene grafted maleic anhydride copolymer, ethylene-ethyl acrylate grafted maleic anhydride copolymer, maleic anhydride grafted styrene-butadiene-styrene block copolymer (styrene may include hydrogenated styrene), polymethyl acrylate, and polyethyl acrylate. Alternatively, the toughening agent may include at least one of ethylene-methacrylate glycidyl copolymer, ethylene-methyl acrylate-methacrylate glycidyl copolymer, ethylene-methyl methacrylate-methacrylate glycidyl copolymer, maleic anhydride grafted styrene-butadiene-styrene block copolymer, polymethyl acrylate, and polyethyl acrylate, such as ethylene-methyl acrylate-methacrylate glycidyl copolymer, maleic anhydride grafted styrene-butadiene-styrene block copolymer, and polyethyl acrylate. Alternatively, the mass percentage of glycidyl methacrylate (GMA) in ethylene-methyl acrylate-methacrylate glycidyl copolymer may be 5wt% to 8wt%, and the mass percentage of maleic anhydride in maleic anhydride grafted styrene-butadiene-styrene block copolymer may be 0.6wt% to 1.1wt%. Alternatively, in the polyphenylene sulfide composition, the content of the toughening agent may be less than or equal to 8 parts by weight, such as 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 parts by weight, etc., and may be 0.1 to 8 parts by weight, or 1 to 5 parts by weight. Controlling the amount of the toughening agent to meet the requirements of the given range is beneficial to further taking into account the comprehensive performance and cost of the polyphenylene sulfide composition.

[0079] Adding a lubricant can improve the demoulding effect when using the polyphenylene sulfide composition to prepare a specific structural part. The lubricant may include but is not limited to at least one of calcium stearate, magnesium stearate, pentaerythritol stearate, polysiloxane, polyethylene wax, hyperbranched resin, oxidized polyethylene wax, silicone, silicone oil, and ethylene bis stearic acid amide. For another example, the lubricant may include but is not limited to Dow Corning silicone masterbatch 4-7081, Dow Corning FCA-107, etc. Optionally, in the polyphenylene sulfide composition, the content of the lubricant may be less than or equal to 1 part by weight, and may be 0.1 to 1 part by weight, such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 part by weight, etc. Controlling the amount of the lubricant to meet the given range requirements is conducive to further taking into account the demoulding effect and cost of the polyphenylene sulfide composition.

[0080] Adding an antioxidant can inhibit the oxidation of the polyphenylene sulfide composition and improve its anti-aging performance. The antioxidant can include at least one of a hindered phenol antioxidant, a phosphite antioxidant, and triphenylphosphine. The hindered phenol antioxidant can include but is not limited to hindered phenol antioxidant 1098 (CAS No.: 23128-74-7), and the phosphite antioxidant can include but is not limited to one or more of antioxidant Ultranox 626 (CAS No.: 26741-53-7), antioxidant 168 (CAS No.: 31570-04-4), and antioxidant PEPQ (CAS: 119345-01-6). Optionally, hindered phenol antioxidants and phosphite antioxidants can be included at the same time, such as hindered phenol antioxidant 1098 as the main antioxidant and phosphite auxiliary antioxidant 168 can be mixed in a weight ratio of 1:1, and the use of the two together can achieve a synergistic effect. Optionally, in the polyphenylene sulfide composition, the content of the antioxidant is less than or equal to 0.5 parts by weight, and can be selected from 0.1 parts by weight to 0.5 parts by weight, such as 0.1, 0.2, 0.3, 0.4 or 0.5 parts by weight, etc. Controlling the amount of the antioxidant to meet the requirements of the given range is beneficial to further taking into account the antioxidant effect and cost of the polyphenylene sulfide composition.

[0081] Adding color powder can make the polyphenylene sulfide composition have the expected color and achieve a specific appearance effect. The color powder can include organic color powder and / or inorganic color powder, wherein the specific type of color powder is not particularly limited, and those skilled in the art can flexibly select it according to actual needs, such as including but not limited to carbon black, etc. Optionally, the content of the color powder is less than or equal to 1wt% of the total mass of the inorganic mineral and the glass fiber, and can be selected from 0.1wt% to 1wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, etc. Controlling the amount of color powder to meet the given range requirements is conducive to further taking into account the appearance effect and cost of the polyphenylene sulfide composition.

[0082] Adding laser engraving additives can use laser to leave a permanent mark on the polyphenylene sulfide composition, which is convenient for product marking. Laser engraving additives can include but are not limited to Honeywell 8825, 8840, etc. Optionally, in the polyphenylene sulfide composition, the content of the laser engraving additive can be 0.3 parts by weight to 1 part by weight, such as 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 part by weight, etc. Controlling the polyphenylene sulfide composition to further include components within the given range is conducive to further improving the performance, appearance effect or processability of the polyphenylene sulfide composition.

[0083] In some embodiments of the present application, the polyphenylene sulfide composition can be obtained by melt-blending various raw material components according to a predetermined ratio.

[0084] As some specific implementation methods, in the actual operation process, the inorganic mineral, polyphenylene sulfide resin and amorphous polymer can be mixed first, and the obtained mixture can be fed from the main feed loss-in-weight scale, and the glass fiber can be added from the side feed loss-in-weight scale, and the blend can be placed in a twin-screw extruder for high-temperature melt extrusion, cooled in a water tank, and granulated. For another example, when the polyphenylene sulfide composition also includes one or more of silane coupling agent, toughening agent, lubricant, antioxidant, color powder, laser engraving agent, etc., the inorganic mineral can be first added to a high-speed mixer and heated to about 90°C, then the silane coupling agent is added and stirred at high speed to fully activate the silane coupling agent, and then the polyphenylene sulfide resin and the non-crystalline polymer are added for blending, such as the speed of the high-speed mixer can be controlled to be 200rpm / min~300rpm / min, and the mixing time is 60s~120s to obtain a premix; then one or more of the toughening agent, lubricant, antioxidant, color powder, laser engraving agent, etc. are added to the premix for mixing, such as the speed of the mixer can be controlled to be 300rpm / min~600rpm / min, and the mixing time is 90s~120s; then the mixture is fed from the main feed weight loss scale, and the glass fiber is added from the side feed weight loss scale, and the blend is placed in a twin-screw extruder for high-temperature melt extrusion, cooled in a water tank, and granulated. Optionally, the conditions of each zone of high-temperature melt extrusion can be: 270℃~300℃ in zone 1; 290℃~310℃ in zone 2; 290℃~310℃ in zone 3; 290℃~310℃ in zone 4; 290℃~310℃ in zone 5; 280℃~300℃ in zone 6; 280℃~300℃ in zone 7; 280℃~290℃ in zone 8; 280℃~290℃ in zone 9; 280℃~300℃ in zone 10; 280℃~300℃ in zone 11; head temperature 280℃~310℃; the temperature difference between the polyphenylene sulfide resin temperature and the barrel temperature of the twin-screw extruder can be less than or equal to 30℃.

[0085] The second aspect of the present application provides a cover, which includes: the polyphenylene sulfide composition of the first aspect of the present application. Optionally, the cover may include a battery pack cover.

[0086] The cover is generally used as a sealing structural part, and has certain requirements for mechanical strength and sealing performance. Taking the battery pack as an example, the battery pack cover is not only required to have good sealing performance and mechanical strength, but also expected to have good flame retardancy and ablation resistance, as well as good dimensional stability, which can extend the time required for melting through and reduce the warpage, and obtain a higher flatness. The use of the polyphenylene sulfide composition of the first aspect of the present application to prepare the cover can not only make the cover have good flame retardancy and ablation resistance, good strength, good dimensional stability, high flatness, which is conducive to improving the sealing effect, but also has good processability, and can be widely used as a packaging structure for products such as batteries, for example, it can be used as a battery pack cover, eliminating the mica paper and edge strips in the battery pack cover.

[0087] In some embodiments of the present application, the cover body 4 may include: a cover plate 41 and a side wall 42. The side wall 42 and the cover plate 41 may be connected to enclose a receiving area. The material of the cover plate 41 and / or the side wall 42 may include the polyphenylene sulfide composition of the first aspect of the present application.

[0088] refer to Figure 1 As shown, in the cover body 4, the side wall 42 and the cover plate 41 can be connected to enclose a containing area, which can accommodate at least a portion of the components to be packaged or the structural parts to be sealed. The material of the cover plate 41 and / or the side wall 42 can include the polyphenylene sulfide composition of the first aspect of the present application. Optionally, the material of the cover plate 41 and the side wall 42 can both include the polyphenylene sulfide composition of the first aspect of the present application. Optionally again, the material of the cover plate 41 and the side wall 42 can only include the polyphenylene sulfide composition of the first aspect of the present application.

[0089] Controlling the cover body to meet the given conditions is conducive to further making the cover body have better flame retardancy and ablation resistance, better strength, good dimensional stability, high flatness, which is conducive to improving the sealing effect and better processability.

[0090] In some embodiments of the present application, the thickness of the cover plate 41 may be ≤3 mm, and may be 2 mm to 3 mm; and / or the thickness of the side wall 42 may be ≤3 mm, and may be 2 mm to 3 mm.

[0091] For example, the thickness of the cover plate 41 can be 3mm, 2.8mm, 2.6, 2.4, 2.2, 2mm, 1.8mm, 1.6, 1.4, 1.2, 1mm, etc., or can be a range consisting of any of the above values; optionally, the thickness of the cover plate 41 can be 2mm to 3mm. The thickness of the side wall 42 can be 3mm, 2.8mm, 2.6, 2.4, 2.2, 2mm, 1.8mm, 1.6, 1.4, 1.2, 1mm, etc., or can be a range consisting of any of the above values; optionally, the thickness of the side wall 42 can be 2mm to 3mm. Due to strength limit restrictions, the thickness of the current plastic cover is generally above 4mm, and it is difficult to make a large thin-walled part. The cover having the polyphenylene sulfide composition of the first aspect of the present application has both good mechanical strength and dimensional stability, and can still have good strength and dimensional stability at a smaller thickness, meeting the demand for high-strength thin-walled plastic parts. Taking the battery pack cover as an example, the thickness of the control cover and side walls is controlled to meet the requirements of the given range. It can not only withstand flame ablation at 1000℃~1100℃ for 10 minutes without melting through and collapse, and there is no need to stick mica paper on the inner wall of the cover, but also has higher strength at a lower thickness, and there is no need to set pressure strips on the edges of the side walls of the cover; optionally, on the basis of not setting pressure strips, the side wall edge strength can be enhanced through structural design; in addition, since the cover has good dimensional stability and low warping, it can also reduce the adverse effects of warping and deformation defects on sealing, thereby improving sealing performance; in addition, since the cover and side walls are thin, it is also conducive to achieving lightweight battery packs and improving energy density.

[0092] In some embodiments of the present application, the cover plate 41 and the side wall 42 are integrally formed.

[0093] Among them, the specific implementation of the integral molding of the cover plate 41 and the side wall 42 is not particularly limited, and those skilled in the art can flexibly choose according to actual needs, for example, it can be obtained by compression molding or injection molding. Optionally, injection molding can be used. The high fluidity of the polyphenylene sulfide composition of the first aspect of the present application can be used to prepare the cover body by injection molding, which is not only efficient, environmentally friendly, and can be recycled and reused many times, but also conducive to controlling the size and achieving lightweight effects. It is especially suitable for the preparation of large thin-walled covers, such as large covers with a size of more than 1.5m. Among them, the high fluidity of the polyphenylene sulfide composition can be obtained by making the ratio of each raw material component meet the requirements of the given range. Optionally, the crystallization temperature and / or melt index of the polyphenylene sulfide resin can also be controlled to meet the given range; Optionally, the fluidity of the polyphenylene sulfide composition can be 110g / 10min~170g / 10min, and meeting the given conditions is further conducive to making a 2mm~3mm thick one-piece thin-walled large cover by injection molding.

[0094] The integrally formed structure of the cover plate and the side wall is beneficial to improving the molding efficiency and further improving the structural stability of the cover body.

[0095] In some embodiments of the present application, the cover body 4 may also be provided with an installation avoidance hole (not shown).

[0096] In some embodiments of the present application, reinforcing ribs (not shown) may be independently provided on the cover plate 41 or the side wall 42 along the length direction of the cover body, thereby facilitating further improving the overall strength of the cover body.

[0097] The third aspect of the present application provides a method for preparing a cover, which comprises: injection molding the polyphenylene sulfide composition of the first aspect of the present application to obtain a cover.

[0098] The use of injection molding technology to prepare the cover is not only efficient, environmentally friendly, and can be recycled and reused many times, but also helps to control the size and achieve a lightweight effect. It is especially suitable for the preparation of large thin-walled covers, such as large covers with a size of more than 1.5m.

[0099] In some embodiments of the present application, when the polyphenylene sulfide composition is injection molded to prepare the cover, the specific injection molding method and molding temperature can be flexibly selected according to actual needs. For example, in-mold insert molding or direct injection molding can be used, and the molding mold temperature can be controlled at 90°C to 120°C.

[0100] The fourth aspect of the present application provides a battery, which includes: the cover body of the second aspect of the present application or the cover body obtained by the preparation method of the third aspect of the present application. Optionally, the battery can be a secondary battery, for example, the battery can be a lithium secondary battery, a sodium secondary battery; further optionally, the battery can be a solid-state battery, etc.

[0101] In some embodiments of the present application, the battery can be a battery cell 1 (refer to Figure 2 It can also be a battery module 2 composed of battery cells 1 (refer to Figure 3 Understand) or battery pack 3 (reference Figure 4 understand).

[0102] In some embodiments, the battery may be a battery module, and the number of battery cells contained in the battery module may be one or more, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 2 is an example of a battery module 2. Figure 3In the battery module 2, the plurality of battery cells 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. The plurality of battery cells 1 may further be fixed by fasteners. Optionally, the battery module 2 may further include a housing having a storage space, and the plurality of battery cells 1 are stored in the storage space.

[0103] In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery module blocks contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Figure 3 or Figure 4 ( Figure 3 and Figure 4 As an example, a battery pack 3 is shown, in which a battery box and a plurality of battery module blocks 2 disposed in the battery box may be included in the battery pack 3. The battery box may include a cover 4 and a lower box 5, and the cover 4 may be covered on the lower box 5 to form a closed space for accommodating the battery module blocks 2. The plurality of battery module blocks 2 may be arranged in the battery box in any manner.

[0104] In some embodiments, the material of the lower box 5 may also include the polyphenylene sulfide composition of the first aspect of the present application.

[0105] In addition, the present application also provides an electrical device, which includes: the battery of the fourth aspect of the present application. The battery, such as a battery cell, a battery module or a battery pack, can be used as both a power source for the electrical device and an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptop computers), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, and energy storage systems. Reference Figure 5 It is understood that, as a specific example, the electric device may be a vehicle. The electric device may select a specific type of battery according to its usage requirements, such as a battery cell, a battery module or a battery pack.

[0106] As an example, the electric device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0107] As another example, the electrical device may be a mobile phone, a tablet computer, or a laptop computer. The electrical device is usually required to be thin and light, and may use a battery cell as a power source.

[0108] In addition, the present application also provides the use of the polyphenylene sulfide composition of the first aspect of the present application in structural parts in the fields of batteries, vehicles, chemicals, ships, and aerospace. The polyphenylene sulfide composition of the first aspect of the present application can be applied to structural parts in the fields of batteries, vehicles, chemicals, ships, aerospace, etc., including but not limited to the upper cover or box structure of energy storage devices such as battery packs, battery pack liners, vehicle protective plates, windshields, fire doors, high-frequency connectors, etc., and is particularly suitable for large upper covers, large flat brackets, or large plastic structural parts with corners and depth that are difficult to prepare in actual production processes, as well as structural parts with high requirements for low warpage, ablation resistance, high strength, etc.

[0109] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0110] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0111] General method for preparing polyphenylene sulfide composition:

[0112] S1: Add inorganic minerals to a high-speed mixer and heat to 90°C, then add a silane coupling agent and stir at high speed for 10 minutes to fully activate the silane coupling agent, then add polyphenylene sulfide resin and non-crystalline polymer, the high-speed mixer speed is 200 rpm / min to 300 rpm / min, the mixing time is 60s to 120s, and a premix is ​​obtained;

[0113] S2: adding a toughening agent, a lubricant, an antioxidant, and a color powder to the premix and mixing to obtain a mixture, wherein the mixer speed is 300 rpm / min to 400 rpm / min, and the mixing time is 90 s to 120 s;

[0114] S3: Feed the mixture from the main feed loss-in-weight scale, and add the glass fiber from the side feed loss-in-weight scale or the reserved long fiber port;

[0115] S4: placing the glass fiber and the mixture in a twin-screw extruder for high-temperature melt extrusion, cooling through a water tank, and granulating to obtain polyphenylene sulfide composition pellets. The high-temperature melt extrusion conditions in each zone are: zone 1 (285±15)℃~300℃; zone 2 (300±10)℃; zone 3 (300±10)℃; zone 4 (300±10)℃; zone 5 (300±10)℃; zone 6 (290±10)℃; zone 7 (290±10)℃; zone 8 (285±5)℃; zone 9 (285±5)℃; zone 10 (290±10)℃; zone 11 (290±10)℃; die head temperature (295±15)℃; the difference between the polyphenylene sulfide resin temperature and the barrel temperature of the twin-screw extruder is less than or equal to 30℃.

[0116] In the following embodiments and comparative examples, steps S1 and S2 are adaptively adjusted according to whether a silane coupling agent, a toughening agent, a lubricant, an antioxidant, or a toner is added.

[0117] Example 1

[0118] The polyphenylene sulfide composition formula: by weight, includes 42 parts by weight of polyphenylene sulfide resin, 10 parts by weight of inorganic minerals, 40 parts by weight of glass fiber, and 10 parts by weight of polystyrene.

[0119] The inorganic minerals are calcium carbonate whiskers, and the glass fibers are flat fibers. The diameter of the flat fibers is 7 μm to 13 μm, and the flatness ratio is less than 1 / 4.

[0120] Examples 2 to 8 and Comparative Examples 1 to 2

[0121] The differences between Examples 2 to 8 and Comparative Examples 1 to 2 and Example 1 are shown in Table 1.

[0122] Examples 9 to 17 and Comparative Examples 3 to 4

[0123] The differences between Examples 9 to 17 and Comparative Examples 3 to 4 and Example 1 are shown in Table 2.

[0124] Embodiments 18 to 28

[0125] The difference between Example 18 and Example 1 is that the polyphenylene sulfide composition formula further includes: a silane coupling agent with a brand of SCA-Y25E, a toughening agent ethylene butyl acrylate (EBA), a lubricant silicone powder, and an antioxidant BASF-1076; the difference between Examples 19 to 28 and Example 18 is that the types of non-crystalline polymers are different. See Table 3 for details. Among them, in Examples 19 to 28, the amount of silane coupling agent used is the mass percentage based on the total mass of the inorganic mineral and glass fiber in each example.

[0126] Performance Testing:

[0127] The following tests were performed on the polyphenylene sulfide compositions prepared in the above-mentioned embodiments and comparative examples. The test results are shown in Tables 1 to 4.

[0128] 1. The warpage test method is as follows:

[0129] The material samples were directly injection molded, and the molding mold temperature was controlled at 90℃~160℃ to obtain a plate with a length and width both greater than or equal to 100mm and a thickness of 2mm. A disc with a thickness of 2mm and a diameter of 80mm was taken from the plate. The disc was placed flat on a horizontal plane, and a weight of about 500g was used to press the warped surface for about 5mm. The height of the other end from the plane was tested with a thickness meter, and the warpage was obtained by subtracting the thickness of the disc from the tested height.

[0130] 2. Melt flow rate

[0131] The test was carried out according to ISO 1133 standard method. The specific operation included: taking 30g of the sample to be tested and drying it in a forced air drying oven at 150℃ for 1h, setting the parameters of the melt index instrument to 316℃ and the test load to 5kg. After the temperature was constant, the dried sample to be tested was added for testing. The sample cutting time interval was 20s, the number of times was 3, and the melt index unit was g / 10min.

[0132] 3. Mechanical properties

[0133] The tensile strength is tested according to ISO527. The total length of the test sample is 150 mm, the end width is 20 mm ± 0.2 mm, the thickness is 4 mm, the width of the middle parallel part is 10 mm ± 0.2 mm, the length of the middle parallel part is 60 mm ± 0.5 mm, the initial clamp spacing is 115 ± 5 mm, the gauge length is 50 mm ± 0.5 mm, the test speed is 5 mm / min, and the unit is MPa.

[0134] The bending modulus is tested according to ISO178 standard method, the test sample length is 80mm±2mm, the width is 10mm±0.2mm, the thickness is 4mm±0.2mm. The selected test speed is 2mm / min, and the unit is MPa.

[0135] The impact strength is tested with reference to the ISO179 standard method, using a 2.75J Charpy notched impact strength. The specific operation is as follows: The impact strength (Charpy notched impact strength test) refers to the test standard ISO 179: Charpy notched impact strength test. The specific operation includes: using an injection molding machine to inject a standard specimen (the specimen length is 80mm±2mm, the width is 10.0mm±0.2mm, and the thickness is 4.0mm±0.2mm), the notch depth is 2mm, and the impact tester is used for testing. The sample is placed in the specified position of the Charpy impact machine, and then the pendulum is used to fall freely to apply an impact load to the sample. The unit is KJ / m 2 .

[0136] 4. Ablation resistance

[0137] Fire-resistant burning test method: Directly injection mold the material sample, control the molding mold temperature at 90℃~160℃, obtain a plate with a length and width greater than or equal to 100mm and a thickness of (2±0.1)mm, place the plate vertically, with the angle between the plate and the horizontal plane at 85 to 95 degrees, and use propane / butane flame to ablate the surface. Use a thermocouple to measure the temperature at the center of the flame on the sample, the flame temperature is required to be 1000℃, and the flame ablation time is 10min.

[0138] The standard for judging the ablation resistance of the plate: no perforation or light transmission after flame ablation for 10 minutes.

[0139] 6. Test of processability and performance of cover during cover preparation

[0140] The material sample was directly injection molded, and the molding mold temperature was controlled at 90℃~160℃ to obtain an upper cover body with a length of 2100mm, a width of 910mm, and a depth of 200mm. The cover body includes a cover plate and a side wall, and the thickness of the cover plate and the side wall is 2.5mm. The injection position pressure and clamping force were recorded, and the deformation of the cover body was tested with the length direction of the cover body as the X direction, the width direction as the Y direction, and the height direction as the Z direction. The test results are shown in Table 4.

[0141]

[0142]

[0143]

[0144] Table 4 Test results of relevant properties of covers prepared by using the PPS compositions in Examples 1, 18, 26 and Comparative Examples 1 and 4

[0145]

[0146] Results and Conclusions:

[0147] Based on the data of Examples 1 to 28, Comparative Examples 1 to 4 and Tables 1 to 4, it can be seen that the polyphenylene sulfide composition of the above-mentioned embodiments of the present application has good ablation resistance, mechanical strength and dimensional stability, and has low warpage. In addition, by further introducing auxiliary materials such as silane coupling agents, toughening agents, and lubricants into the polyphenylene sulfide composition, it is beneficial to further improve the comprehensive performance of the polyphenylene sulfide composition. The cover body made of the polyphenylene sulfide composition in Examples 1, 18 and 26 is not provided with a pressure strip, and not only has low warpage, but also has good strength. Furthermore, appropriately adjusting the amount of each component in the polyphenylene sulfide composition is beneficial to further comprehensively improve the ablation resistance, mechanical strength and dimensional stability of the polyphenylene sulfide composition. For example, in combination with Examples 1, 5 to 8 and Comparative Examples 1 to 2, it can be seen that appropriately increasing the amount of non-crystalline polymer is beneficial to improving the fluidity and warpage of the polyphenylene sulfide composition while taking into account both mechanical properties and ablation resistance; for another example, in combination with Examples 1, 9 to 13 and Comparative Examples 3 to 4, it can be seen that appropriately increasing the amount of glass fiber is beneficial to further improve the mechanical properties and ablation resistance of the polyphenylene sulfide composition. Appropriately increasing the amount of inorganic minerals is beneficial to improving the warpage and impact strength of the polyphenylene sulfide composition, and is also beneficial to forming an effective network support skeleton with glass fiber at high temperature, thereby further improving the ablation resistance. Furthermore, appropriately adjusting the amount of each component in the polyphenylene sulfide composition or the melt index of the polyphenylene sulfide composition is also beneficial to improving the polyphenylene sulfide composition to have a moderate melt index, thereby obtaining better high-temperature fluidity, improving processability and warpage, and facilitating injection molding (further, in combination with Table 4, it can be seen that with the increase of the melt index of the polyphenylene sulfide composition, the pressure and clamping force at the injection position during the injection molding process are also smaller, indicating better processability), and can also reduce the risk of the composition being prone to melt through at high temperatures due to excessive fluidity. In combination with Example 1, It can be seen from Examples 14 to 17 and Comparative Examples 3 to 4 that appropriately increasing the melt index of polyphenylene sulfide can improve the fluidity of the composition and obtain better ablation resistance. Optionally, the melt index of the polyphenylene sulfide composition can be 600 g / 10min to 800 g / 10min. In addition, it can be seen from Examples 18 to 28 that changing the type of non-crystalline polymer can also make the polyphenylene sulfide composition have better ablation resistance, mechanical strength and lower warpage, and compared with using PEN and PS alone, mixing the two is beneficial to further improve the comprehensive performance of the composition.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A polyphenylene sulfide composition, characterized in that: include: 30 to 60 parts by weight of polyphenylene sulfide resin, 10 to 30 parts by weight of inorganic mineral, 30 to 40 parts by weight of glass fiber, and 5 to 15 parts by weight of non-crystalline polymer.

2. The polyphenylene sulfide composition according to claim 1, characterized in that: include: 30 to 45 parts by weight of the polyphenylene sulfide resin, 10 to 25 parts by weight of the inorganic mineral, 35 to 40 parts by weight of the glass fiber, and 8 to 12 parts by weight of the non-crystalline polymer.

3. The polyphenylene sulfide composition according to claim 1 or 2, characterized in that: The crystallization temperature of the polyphenylene sulfide resin is less than or equal to 225° C.; and / or, The melt index of the polyphenylene sulfide resin at a temperature of 316° C. and a mass of 5 kg is 400 g / 10 min to 1200 g / 10 min, and can be optionally 600 g / 10 min to 800 g / 10 min.

4. The polyphenylene sulfide composition according to any one of claims 1 to 3, characterized in that: The non-crystalline polymer includes at least one of polystyrene, polyarylethernitrile, polyphenylene oxide, polysulfone, polyetherimide, polyphenylene sulfone, polyethersulfone or polyimide. Optionally, the non-crystalline polymer includes polystyrene and / or polyarylethernitrile.

5. The polyphenylene sulfide composition according to any one of claims 1 to 4, characterized in that: The glass fibers include short fibers and / or flat fibers.

6. The polyphenylene sulfide composition according to claim 5, characterized in that: The short fibers have a length of 3 mm to 4.5 mm and a diameter of 7 μm to 13 μm; and / or the flatness ratio of the flat fibers is less than or equal to 1 / 4 and the diameter is 7 μm to 13 μm.

7. The polyphenylene sulfide composition according to any one of claims 1 to 6, characterized in that: The polyphenylene sulfide composition further includes: a silane coupling agent. Based on the total mass of the inorganic mineral and the glass fiber, the mass percentage of the silane coupling agent in the inorganic mineral and the glass fiber is ≤1wt%, and can be optionally 0.5wt% to 1wt%.

8. The polyphenylene sulfide composition according to any one of claims 1 to 7, characterized in that: Also includes: At least one of a toughening agent, a lubricant, an antioxidant, a toner or a laser engraving aid.

9. A cover, characterized in that: The material of the cover comprises the polyphenylene sulfide composition according to any one of claims 1 to 8.

10. The cover according to claim 9, characterized in that: The cover body comprises: a cover plate and a side wall, wherein the side wall is connected to the cover plate to enclose a containing area, and the material of the cover plate and / or the side wall comprises the polyphenylene sulfide composition according to any one of claims 1 to 8.

11. The cover according to claim 10, characterized in that: The thickness of the cover plate is ≤3 mm, and can be 2 mm to 3 mm; and / or, The thickness of the side wall is ≤3 mm, and may be 2 mm to 3 mm; and / or, The cover plate and the side wall are integrally formed.

12. A method for preparing a cover, characterized in that: include: The polyphenylene sulfide composition according to any one of claims 1 to 8 is injection molded to obtain a cover.

13. A battery, characterized in that: The invention comprises the cover body according to any one of claims 9 to 11 or the cover body obtained by the preparation method according to claim 12.

14. An electrical device, characterized in that: Comprising the battery of claim 13.

15. Use of the polyphenylene sulfide composition according to any one of claims 1 to 8 in structural parts in the fields of batteries, vehicles, chemicals, ships, and aerospace.

Citation Information

Patent Citations

  • Glass fiber reinforced polyphenylene sulfide / polyphenyl ether composite material and preparation method thereof

    CN103509343A

  • Polyphenylene sulfide resin composition and molded product thereof

    CN104650584A

  • Fiber reinforced PPS / PS composite material and product thereof

    CN105086451A

  • High-flowability high-rigidity polyphenylene sulfide resin compound and product thereof

    CN106147230A

  • High-precision low-overflow low-warpage low-dielectric PPS modified material and preparation method thereof

    CN112679956A